Elisions and lacunae: aspects of South African landscape in relation to public and private identities - Farlam, Catherine Mary (Michaelis School of Fine Art, 2023)
This project is concerned with articulating a number of positions around meaning and hegemony in museums and how such relationships can be refigured. It looks at how texts have been written in a unique exhibition in South Africa, the William Fehr Collection at the Castle. This Collection is unique in that the specific conditions of its sale to the state in 1964 determine its function as a museum within a museum. It is also unique in that its first public showing was as part of the Jan van Riebeeck Tercentenary Festival of 1952, where it formed the bulk of a Historical Exhibition of Arts at the Castle. I examine how meanings are constructed in the Collection, and how these meanings gain authority in abstract terms through conceptualising space in particular ways. I argue that how space is conceptualised forms a site of critical intervention. I counter the notion of absolute space with a commitment to mobile positioning. To do this, I look at how landscape conventions at Table Bay (wellrepresented in the Collection) apparently construct a singular position, extending this into an examination of how meanings have been refigured in museums by a number of conceptual artists. I suggest that this project can be extended into a physical intervention in the form of an audio-tour through the Collection. I have produced such an acoustiguide entitled A Passage through the William Fehr Collection. This thirty-five minute tour is available from the Professional Officer of the William Fehr Collection at the Castle.